2020
DOI: 10.1186/s12916-020-01536-7
|View full text |Cite
|
Sign up to set email alerts
|

The long-term health effects of attending a selective school: a natural experiment

Abstract: Background: Education is widely associated with better physical and mental health, but isolating its causal effect is difficult because education is linked with many socioeconomic advantages. One way to isolate education's effect is to consider environments where similar students are assigned to different educational experiences based on objective criteria. Here we measure the health effects of assignment to selective schooling based on test score, a widely debated educational policy. Methods: In 1960s Britain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…3 ) but these seemed not to translate into reduced health inequalities. Similarly, recent UK research comparing outcomes in the selective system only for those who could have gone to an academic school, based on having a cognitive ability score near the cut off but some of whom did not obtain a place, found evidence of effects on education by school type but no effects on health ( Butler et al, 2020 ; Clark and Royer, 2013 ; Pastore & Jones, 2019 ). While there was evidence of educational inequalities in BMI being lower in one cohort, across the other health outcomes there was little difference between the school systems whether we assessed inequality by education or social class.…”
Section: Discussionmentioning
confidence: 96%
“…3 ) but these seemed not to translate into reduced health inequalities. Similarly, recent UK research comparing outcomes in the selective system only for those who could have gone to an academic school, based on having a cognitive ability score near the cut off but some of whom did not obtain a place, found evidence of effects on education by school type but no effects on health ( Butler et al, 2020 ; Clark and Royer, 2013 ; Pastore & Jones, 2019 ). While there was evidence of educational inequalities in BMI being lower in one cohort, across the other health outcomes there was little difference between the school systems whether we assessed inequality by education or social class.…”
Section: Discussionmentioning
confidence: 96%
“…Fewer studies have explicitly addressed this association between the type of education and subsequent health. [19][20][21][22] Using self-rated health in mid-adulthood as the main outcome measure, most studies have found a small association between attending a selective school and subsequent health, with those attending more selective schools reporting higher self-reported health. [19][20][21][22] The magnitude and direction of the associations tend to vary across different health outcomes and few used objective measures.…”
Section: Original Researchmentioning
confidence: 99%
“…[19][20][21][22] Using self-rated health in mid-adulthood as the main outcome measure, most studies have found a small association between attending a selective school and subsequent health, with those attending more selective schools reporting higher self-reported health. [19][20][21][22] The magnitude and direction of the associations tend to vary across different health outcomes and few used objective measures. It was also found that attending an advantageous secondary school or a highly selective university was associated with better cognitive function in old age.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the trials included was from PLOS One. To date, BMC Medicine has only published 3 Registered Reports (16)(17)(18), none concerned a clinical trial.…”
Section: Statement Of Principal Findingsmentioning
confidence: 99%